Attitude of entrepreneurs in Iloilo City towards Chinese beliefs and practices - Azucena, Michelle Dawn.; Baguioro, Sharlyn Dawn.; de la Torre, Mae.; Lomigo, Aubrey; Mamon, Levi. (2005.)
This study aimed to determine the attitude of entrepreneurs in Iloilo City towards Chinese beliefs and practices. The researchers limited the study to sole proprietorship, type of business, which has sustained operations for 5 to 10 years. To be able to give emphasis on the study, the researchers covered businesses engaged in merchandising and located in Ledesma, Iznart, JM Basa, Delgado, Guanco, Aldeguer, Quezon, Valeria, Mapa and De Leon streets. Specifically, the study aimed to answer the following questions: 1) What are the Chinese business beliefs and practices of entrepreneurs in Iloilo City? ; 2) What is the attitude of entrepreneurs in Iloilo City towards Chinese business beliefs and practices ; 3)Is there a significant difference in the Chinese business beliefs and practices of entrepreneurs in Iloilo City when they are grouped according to age, sex, educational attainment, ethnic roots, and business history? ; 4) Is there a significant difference in the attitude of entrepreneurs in Iloilo City towards Chinese business beliefs and practices when grouped according to age, sex, educational attainment, ethnic roots, and business history? ; 5) Is there a co relationship between the Chinese beliefs and practices and Attitude of entrepreneurs in Iloilo City? with the questions stated above, the researchers have made several hypotheses which are non-directional : 1) There is no significant difference in the Chinese business beliefs and practices of entrepreneurs in Iloilo City when they are grouped according to age, sex, educational attainment, ethnic roots, and business history ; 2) There is no significant difference in the attitude of entrepreneurs in Iloilo City towards Chinese business beliefs and practices when grouped according to age, sex, educational attainment, ethnic roots, and business history ; 3) There is no co relationship between the Chinese beliefs and practices and attitudes of entrepreneur in Iloilo City. The descriptive method of research was used in this study. Data were gathered using a questionnaire. There were 30 respondents, and the purposive method of sampling was used. The respondents were then grouped according to age, sex, educational attainment, ethnic roots, and business history. The data was then subjected to the following statistical tools : Frequency Distribution, Means, Kruskall-Wallis H-test and the Mann-Whitney U Test. In light of the findings, the following conclusions were then made : 1) There is significant difference in the Chinese business beliefs on lucky and unlucky colors of entrepreneurs in Iloilo City when they are grouped according to ethnic root ; 2) There is significant difference in the responses of entrepreneurs in Iloilo City for the following reason for using Chinese beliefs and practices in the conduct of their business : b) I was dictated by my parents and other members of the family when they were grouped according to educational attainment ; 3) There is significant difference in the responses of entrepreneurs in Iloilo City for the following importance for using Chinese beliefs and practices in the conduct of their business : c) major factor in development of character when they were grouped according ethnic root ; 4) There is significant difference in the responses of entrepreneurs in Iloilo City for the following perceived effects of using Chinese beliefs and practices in the conduct of their business d) bring harmony to personnel when they were grouped according to sex ; 5) There is significant difference in the responses of entrepreneurs in Iloilo City for the following perceived effects of using Chinese beliefs and practices in the conduct of their business a) bring in more customers when they were grouped according to ethnic root ; 6) There is a significant difference in the responses of entrepreneurs in Iloilo for the following perceived effects of using Chinese beliefs and practices in the conduct of their business c) increase profit and cash flow when they were grouped according to business history ; and 7) There is significant co-relationship between the Chinese business beliefs and practices of entrepreneurs in Iloilo City and their attitude towards those beliefs and practices.
Research Study (BA 200 - Business Research) -- Iloilo City : Uniersity of the Philippines in the Visayas-College of Management, March 21, 2005. March 21, 2005.